PENENTUAN SIFAT HIDROFOBIK DAN HIDROFILIK BAHAN DENGAN METODE SUDUT KONTAK - husain husain; Herlinda Herlinda (JSAI (Journal Scientific and Applied Informatics), 2022)
The contact angle is the angle formed between the droplet and the surface of the solid object that is in contact when the droplet is dropped on the surface of the material. In environmental conditions with high pollution and high humidity, the layer of pollutants attached to the surface occurs wetting so that the leakage current that flows can cause heating of the pollutants in the layer. This layer can form a dry band due to continuous leakage current. Conditions at certain voltages can cause discharge across the dry band. The discharge arc can extend so that flashover occurs across the entire surface of the insulator. This study aims to design a measuring instrument to determine hydrophobic and hydrophilic insulating materials. The research was conducted using the water drop method on the insulating material and then analyzed using the contact angle equation. The process of measuring the contact angle of water droplets (droplets) is carried out using an application designed with the Borland Delphi programming language. The results showed that polymeric materials that did not contain pollutants showed a contact angle of 900 meaning that the material was hydrophobic or not water-loving, while those with pollutants showed a contact angle below or <900, meaning that the material was hydrophilic (water-loving).